Setting priorities and reducing uncertainties for the treatment of vitiligo - Eleftheriadou, Viktoria (2013)
Vitiligo is the most common skin disorder resulting in depigmentation, but high-quality research is lacking. A Cochrane review of interventions for vitiligo published in 2010 highlighted methodological limitations with existing trials; which have generally been too small and heterogeneous to inform clinical recommendations.